Didactics of Literature: Literary Teaching as a Form of Contagion - Altamirano Flores, Federico (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The objective of this article is to propose a strategy of contagion of literature as a means for practical intervention in the literary education of students. We propose aesthetic modeling as a pertinent strategy to transmit the passion for literature. This proposal is based in the theory of literary contagion, dialogical pedagogy and general aesthetics. The formulation of this strategy is inspired, on the one hand by Bandura ́s concept of cognitive modeling, and on the other, by the pedagogical experiences of the writer Vladimir Nabokov and his successful experience in literary education. Through an analysis of the classes and testimonies of Nabokov, we offer the concept of “aesthetic modeling”, with its corresponding didactic procedures, as an alternative didactic strategy for educating the literary sensibility of students